ANALISIS KEKERASAN SAMBUNGAN LAS MIG BAJA KARBON RENDAH DENGAN BERBAGAI VARIASI KAMPUH - Ishak, Sahianol; Rauf, Wawan (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
Along with technological developments, the use of metals such as steel cannot be separated from the welding process. Where welded joints have advantages in the form of lightweight construction, able to withstand high loads, and are more economical. One of the factors that must be considered in producing a good welded joint is the weld camp. Welding camp are used to accommodate filler material on the metal, so that the determination of the type of camp is based on the needs of the construction being built. The purpose of this study was to analyze the hardness of low carbon steel MIG welded joints with various variations of camp and welding temperature. The test material used was ST 37 low carbon steel with a thickness of 6 mm and a width of 100 mm. Tests were carried out to compare the weld joint hardness values with the application of V, I, and K seams on each welding electric current of 130 A, 150 A, and 170 A. The test results showed that in all types of seams, the higher the welding electric current. Applied, the greater the hardness value of the welded joint obtained. The highest hardness value was obtained at a welding current of 170 A with a V camp of 89.8 N/mm2.